2014
DOI: 10.12965/jer.140090
|View full text |Cite
|
Sign up to set email alerts
|

The effect of push factors in the leisure sports participation of the retired elderly on re-socialization recovery resilience

Abstract: This study aimed to provide useful materials for the realization of healthy and happy welfare society through the re-socialization of the retired elderly by identifying the effect of the push factors in the leisure sports participation of the retired elderly on re-socialization and recovery resilience. To achieve the study purpose, 304 subjects over the age of 55 residing in Seoul and Gyeonggin among the retired elderly were selected by using the method of systematic stratified cluster random sampling. As rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…19,11 Internationally, there is evidence that the participation of the elderly in group activities have a positive effect on health and on the quality of life of this population, indicating that these individuals are healthier in terms of cognition, behavior, psychological, social involvement and physical and medical health. 20 Still, with regards to health improvements, it was evidenced that the elderly participants of the study emphasized the participation in the conviviality group as an important factor in the improvement of mental health, referred to mostly as "head health", and also as a form of prevention and treatment of depression, being one of the reasons that led them to attend the group, as it portrays the following statements:…”
Section: Conviviality Groups As a Learning Space For Elderly Peoplementioning
confidence: 97%
“…19,11 Internationally, there is evidence that the participation of the elderly in group activities have a positive effect on health and on the quality of life of this population, indicating that these individuals are healthier in terms of cognition, behavior, psychological, social involvement and physical and medical health. 20 Still, with regards to health improvements, it was evidenced that the elderly participants of the study emphasized the participation in the conviviality group as an important factor in the improvement of mental health, referred to mostly as "head health", and also as a form of prevention and treatment of depression, being one of the reasons that led them to attend the group, as it portrays the following statements:…”
Section: Conviviality Groups As a Learning Space For Elderly Peoplementioning
confidence: 97%
“…Diversos estudios muestran que la práctica regular de deporte durante la niñez y la adolescencia contribuye a la adquisición de habilidades sociales como la cooperación, la búsqueda de derechos, la conciencia de las responsabilidades, el establecimiento de la empatía, el autocontrol y el liderazgo; como consecuencia, el nivel de agresividad disminuye y se mantienen relaciones positivas entre pares (Perron-Goinas, Brendgen & Vitaro, 2017;Shachar, et al 2016;Calero et al, 2017;Inoue et al, 2018;Kavussanu & Stanger, 2017). Además, las actividades deportivas animan a los niños a ayudar a los demás y a desarrollar altruismo y empatía (Lee et al, 2014). También, se ha observado que los adolescentes que practican deportes son más amigables con sus compañeros, especialmente con aquellos que participan en actividades similares, y tienen menos contacto con sus compañeros que están inclinados a participar en conductas antisociales (Jodra et al, 2018).…”
Section: Introductionunclassified
“…In addition to these, it is considered that socializing through sports activities in old age period contributes to social skills such as empathy and control of impulses; and affects the self-sufficiency levels of individuals in a positive manner (Lee, Kim & Yi, 2014). Nevertheless, it is observed that the relationship between sporting and social isolation is negatively related to the social life in the aging period, and individuals dealing with sports show more participation in social life (Gayman, Fraser-Thomas, Dionigi, Horton & Baker, 2017;Toepoel, 2013).…”
mentioning
confidence: 99%